Assessment of salivary ph in patients with oral leukoplakia - CHAITHANYA.V, DR. MUKUNDH; MAHESWARI.T. N, DR. UMA (The journal of contemporary issues in business and government, 2020)
Saliva is an important and a complex secretion to be formed in the oral cavity. Salivary pH was done in patients with the presence of leukoplakia and a comparison is done to estimate the salivary pH in patients with leukoplakia and in healthy subjects, though saliva pH has an effect based on the usage of tobacco products and other substances, this study is done to prove that saliva can be used as a diagnostic tool in identifying the lesion which are pre-malignant based on changes in pH. The results of the study show that there is a significant decrease in the mean pH of Saliva in patients with tobacco consumption as compared with non-users, though there are other studies that show in contrast, this study is done to prove the significance of salivary pH change in users of smokeless and smoking in patients with oral leukoplakia. Association analysis of mean pH of patients with oral leukoplakia and Type of leukoplakia shows no statistical significance(Chi-square: 30.000, p value: 0.414 > 0.05).